Celebrating Ethiopia's agricultural transformation - International Livestock Research Institute (International Livestock Research Institute, 2019)
Ethiopia has made unprecedented investments in agriculture in the past two decades. As a result, the agriculture sector is growing 7% annually and millions of Ethiopians are now rising to a middle-class life, moving out of poverty and hunger. CGIAR is working alongside the Ethiopian people in their agricultural transformation.